An improved adaptive shuffled frog leaping algorithm to solve various non smooth economic dispatch problems in power system / Mohamad Helmi Muhamad Izham - Muhamad Izham, Mohamad Helmi (2016)
This thesis discusses the solution of Economic Dispatch (ED) problems which is to minimize the total cost of generation in power system operation by using an improved adaptive shuffled frog leaping algorithm (lASFLA). IASFLA is inspired from the behavior of a group of frogs to search a food source, is an optimization technique that has been developed for solving the various problems. In this study, the IASFLA is suggested in order to improve the local search and performance of SFLA for nonsmooth optimization problem with non-convex solution spaces. The proposed IASFLA method is developed using MATLAB programming. The IASFLA method is tested on a ten generator units system with valve-point loading effects and multifuel source options. The results obtained proved that IASFLA is able to solve the problem with minimum total cost of generation compared to other methods.